-10521=35n

Rewrite the equation as 35n=-10521.

35n=-10521

Divide 105 by 21.

35n=-1⋅5

Multiply -1 by 5.

35n=-5

35n=-5

Multiply each term by n and simplify.

Multiply each term in 35n=-5 by n.

35n⋅n=-5⋅n

Cancel the common factor of n.

Cancel the common factor.

35n⋅n=-5⋅n

Rewrite the expression.

35=-5⋅n

35=-5n

35=-5n

Rewrite the equation as -5n=35.

-5n=35

Divide each term by -5 and simplify.

Divide each term in -5n=35 by -5.

-5n-5=35-5

Cancel the common factor of -5.

Cancel the common factor.

-5n-5=35-5

Divide n by 1.

n=35-5

n=35-5

Divide 35 by -5.

n=-7

n=-7

n=-7

Solve for n -105/21=35/n